Pengaruh Banyaknya Radiasi dan Perubahan Energi Sinar-X terhadap Peningkatan Pembentukan Radikal Bebas pada Air - Muhammad Fakhrurreza; Puput Khusniatul Mujidah (Universitas 'Aisyiyah Yogyakarta, 2018)
The method used in the research was quantitative that was experimenting on water (H2O), which was subjected to x-ray radiation with tube voltage variation and calculating the level of peroxide (H2O2) in water that has been exposed to radiation. The study was conducted by irradiating one liter of water added with five milliliters of KMnO4 and one milliliter of H2SO4 as a catalyst with tube voltage variation of 40 kV, 60 kV and 80 kV with 200 mSec and 400 mA of 10 irradiation times. The analysis was performed using a spectrometer. The results find that the more radiation, the higher the free radicals are formed. While the higher the x-ray energy, the fewer free radicals are formed.